2022
DOI: 10.1038/s41598-022-23497-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value and antioxidant capacity of organic and conventional vegetables of the genus Allium

Abstract: There are indications that organically grown plants are safer for health and have higher antioxidant content than conventional ones. Vegetables of the genus Allium L. are a valuable source of health-promoting substances, including compounds with antioxidant properties. The aim of the study was to compare the antioxidant potential and nutritional value of four species of Allium L. vegetables obtained from organic and conventional production: garlic, leek and red and yellow onion. Their proximate and mineral com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…23 The antioxidant activities were high in the ABTS assay of hydroponically grown green and red lettuce because the quality of the free radical scavenger is different. Geneva et al ( 2021) 24 reported that NPK is essential for lettuce growth and increases antioxidant capacity. They tested the FRAP assay but the DPPH assay showed less activity, while we found that DPPH showed the highest activity.…”
Section: Resultsmentioning
confidence: 99%
“…23 The antioxidant activities were high in the ABTS assay of hydroponically grown green and red lettuce because the quality of the free radical scavenger is different. Geneva et al ( 2021) 24 reported that NPK is essential for lettuce growth and increases antioxidant capacity. They tested the FRAP assay but the DPPH assay showed less activity, while we found that DPPH showed the highest activity.…”
Section: Resultsmentioning
confidence: 99%
“…As studies have shown, organic products not only contain more antioxidants ( 11 16 ), but also calcium ( 62 – 67 ), iron ( 17 , 19 , 68 , 69 ), manganese ( 70 , 71 ), as well as vitamins: E ( 19 , 72 , 73 ) and C ( 11 , 70 72 , 74 ), although some studies on calcium ( 70 ), iron ( 62 , 70 , 75 ) and vitamin C ( 76 , 77 ) gave different results. Equivocal results were obtained for phosphorus ( 78 , 79 ), magnesium ( 66 , 67 , 70 , 78 , 80 ), copper ( 66 , 70 ), and a significant number of studies showed lower zinc ( 70 , 71 , 79 ) and folate content ( 77 ) in the case of organic farming. Rationally assuming that organic orchardists are more likely to consume the food they produce ( 6 ), then the content of selected minerals and vitamins is likely to be even higher.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that organic fruits contain more bioactive compounds than conventional fruits (Hamouz et al 2013;Jurica, Petříková 2014;Średnicka-Tober et al 2020;Breza-Boruta et al 2022;Czech et al 2022). This is expected, considering the fact that the use of synthetic pesticides in organic agriculture is restricted and, therefore, plants tend to produce more or higher levels of bioactive compounds protecting them against pests, diseases and oxidative damage (Dragišić Maksimović et al 2013;George et al 2021).…”
Section: Methodsmentioning
confidence: 99%